Climate Change-Induced Emergence of Novel Biogeochemical Provinces - Reygondeau, Gabriel; Cheung, William W. L.; Wabnitz, Colette C. C.; Lam, Vicky W. Y.; Frölicher, Thomas; Maury, Olivier (Frontiers in Marine Science, 2020)
The global ocean is commonly partitioned into 4 biomes subdivided into 56 biogeochemical provinces (BGCPs) following the accepted partition proposed by Longhurst in 1998. Each province corresponds to a unique regional environment that shapes biodiversity and constrains ecosystem structure and functions. BGCPs are dynamic entities that change their spatial extent and position with climate and are expected to be pertubated in the near future by global climate change. Here, we characterize the changes in spatial distribution of BGCPs from 1950 to 2100 using three earth system models under two representative concentration pathways (RCP 2.6 and 8.5). We project a reorganisation of current distribution of BGCPs driven mostly by a poleward shift of their distributions (18.4 km in average per decade). Projection of the future distribution of BGCPs also revealed the emergence of new climate that has no analogue with past and current environmental conditions experienced by BGCPs . This novel environmental conditions, here named No-Analogue BGCPs State (NABS), will expand from 2040 to 2100 at a rate of 4.3 Mkm2 per decade (1.2% of the global ocean). We subsequently quantified the potential amount of marine species and fisheries catch that would experience such novel environmental conditions to roughly evaluate NABS impact on ecosystem services.